Answer:
D, E, C, A, and B.
Step-by-step explanation:
We wish to solve the equation:
[tex]2(x-3)+7-3x=11[/tex]
Let’s go through this step-by-step.
1) Distributive Property:
[tex]2x-6+7-3x=11[/tex]
2) Commutative Property of Addition (we rearrange them):
[tex]2x-3x-6+7=11[/tex]
3) Combined Like Terms:
[tex]-x+1=11[/tex]
4) Addition Property of Equality* (we add -1 to both sides):
[tex]-x=10[/tex]
5) Multiplication Property of Equality (we multiply both sides by -1):
[tex]x=-10[/tex]
So, our sequence is:
D, E, C, A, and B.
*A better choice would’ve been the Subtraction Property of Equality, but both are equally fine.